Role of the degradation process in the mitogenic effect of epidermal growth factor - Savion, Naphtali (1980)
The protease inhibitor leupeptin inhibits the degradation process of (125)I-labeled epidermal growth factor ((125)I-EGF) by cultured bovine granulosa cells. At 80 μg/ml, leupeptin inhibited the appearance of degradation products of (125)I-EGF in the medium by 95% during 1 hr of incubation and by 90% during 24 hr of incubation when the cells were exposed to 5 ng of (125)I-EGF per ml. In contrast, cultures exposed to either saturating (10 ng/ml) or nonsaturating (0.1 ng/ml) concentrations of EGF in the presence of leupeptin (80 μg/ml) exhibited an increase in DNA synthesis that was 70-80% that of cultures exposed to EGF alone. Cultures responded to either EGF or fibroblast growth factor with a logarithmic increase in cell number and, over a period of 8 days, the number of cells increased 10- to 18-fold. Addition of leupeptin did not diminish the growth rate of the cultures. In the presence of leupeptin, (125)I-EGF accumulated within the granulosa cells and was in a form that was precipitable with antiserum against EGF and that comigrated on isoelectric focusing with native (125)I-EGF. That a full mitogenic response can be obtained despite a 90-95% inhibition of EGF degradation at either saturating or nonsaturating concentrations of the mitogen suggests that a proteolytic degradation of a given mitogen may not be involved in the induction of a proliferative response.